THE ANALYSIS OF BALANCED POLICIES IN WAQF BASED FINANCIAL MANAGEMENT ON PRIVATE HIGHER EDUCATION IN WEST JAVA - Warizal; Gursida, Hari; Sasongko, Hendro (jfpublisher, 2023)
The main problem for private universities in Indonesia is the ability to finance the institution's operations independently and the main source of income for financing is still sourced from tuition fees paid by students. For waqf-based private universities, another problem is that assets cannot be used as collateral to obtain funding assistance from financial institutions. This situation causes waqf-based private universities to strive to manage finances properly for there is no waste and fraud. The purpose of this research was to examine the effect of transformational leadership, organizational commitment and competence of financial human resources through a balanced budget policy on the effectiveness of waqf-based private university financial management. The research method used was explanatory, and the data were collected using a questionnaire given by waqf-based private university financial leaders and staff, then analyzed using Partial Least Square (PLS) approach. The results of the research shows that balanced budget policies mediate transformational leadership, organizational commitment, financial HR competence have a positive influence on Financial Management Effectiveness as illustrated by t-statistic value (4.021) > 1.66 with a p-value (0.000) <0.05. Waqf-based private universities can increase the effectiveness of financial management through a balanced budget policy model in accordance with the characteristics of the institution supported by proper leadership, organizational commitment and competence of financial human resources which are continuously improved.